AB1042 A Comparison of Ultrasound Versus Nerve Conduction Studies for the Diagnosis of Carpal Tunnel Syndrome. (9th June 2015) - McDonagh, C.; Alexander, M.; Kane, D.
Abstract : Background: Carpal tunnel syndrome (CTS) is the commonest entrapment neuropathy. (1, 2) Sensitivity and specificity of ultrasound (US) to diagnose carpal tunnel syndrome has been reported to be as high as 97.9% and 100% respectively using measurement of the cross-sectional area (CSA) of the median nerve (3), while nerve conduction studies (NCS) have a sensitivity and specificity of >85% and >95% respectively.(4) Objectives: To document the sensitivity and specificity of US to diagnose CTS in comparison to NCS and to establish a new pathway for diagnosis of CTS using US. To assess the ability of US and NCS to assess the response to treatment with corticosteroid injection. Methods: Patients with clinically confirmed idiopathic CTS were recruited from outpatient clinics. They were assessed clinically, by US including power Doppler (PD) and NCS. Clinical diagnosis was the reference standard. Patients received treatment with corticosteroid injection and outcome was assessed using the Levine Katz questionnaire (LKQ) and visual analogue score (VAS) for pain. Results: There were 29 patients (40 wrists) and 12 controls (23 wrists) recruited into the study. Results of sensitivity and specificity of US and NCS to diagnose CTS are displayed in Table 1 . Only PD showed a significant correlation with change in LKQ score and VAS at 6 weeks following injection but not at 6 months (p=0.047 and 0.008 for LKQ and 0.015 and 0.05 for VAS). Conclusions: Sensitivity of US is the same as NCS in this study but NCS has a higher specificity. Increasing the cut-off for diagnosis of CTS using CSA increases the specificity of US but reduces the sensitivity. CSA≥10mm 2 and/or PD signal gave the best sensitivity for US. Greyscale US and NCS did not correlate with scores on LKQ, however PD correlated with subjective measures at 6 weeks only. A new paradigm for diagnosis of CTS incorporating US is proposed. References: de krom M, Knipschild P, Kester A, Thijs C, Boekkooi P, Spaans F. Carpal tunnel syndrome: prevalence in the general population. J Clin Epidemiol. 1992;45:373-6. Bongers F, Schellevis F, van den Bosch W, van der Zee J. Carpal tunnel syndrome in general practice (1987 and 2001): Incidence and the role of occupational and non occupational factors. Br J Gen Pract. 2007;57:36-9. El Miedany Y, Aty S, Ashour S. Ultrasonography versus nerve conduction study in patients with carpal tunnel syndrome: substantive or complementary tests? Rheumatology. 2004;43(7):887-95. Jablecki C, Andary M, So Y, Wilkins D, Williams F. Literature review of the usefulness of nerve conduction studies and electromyography for the evaluation of patients with carpal tunnel syndrome. AAEM Quality Assurance Committee. Muscle and Nerve. 1993;16:1392-414. Disclosure of Interest: None declared